The religious and cultural landscape of Ottoman Manastır - Mihajlovski, Robert. (Leiden ; Boston)
xiii, 309 sayfa
Keywords: “In this ground-breaking work on the Ottoman town of Manastir (Bitola), Robert Mihajlovski, provides a detailed account of the development of Islamic, Christian and Sephardic religious architecture and culture as it manifested in the town and precincts. Originally a town on the edge of the Via Egnatia, this small provincial town gradually developed into a significant administrative, military, religious, cultural and intellectual centre for the Balkans; a vibrant place, nurturing progressive multi-cultural and multi-confessional values with considerable influence on the formation of modern Balkan identities. The present work is the culmination of thirty years of research using primary source material from archives and chronicles and the monuments themselves for the purpose of both preserving and extending the boundaries of current knowledge. It offers a comprehensive biography of a great cultural knot in the Balkans and offers a rich source for further use by scholars, students and non-technical readership alike“ --